Character Development of Students through an English Literacy Program Based on Storytelling - Sulastri, Sulastri; Ratnawati, Ratnawati; Abdollah, Abdollah; Hudriati, Andi; Am, St. Asriati. (Edumaspul: Jurnal Pendidikan, 2023)
The literacy program is a strategy implemented by schools worldwide with the aim of making their citizens literate for a lifetime. This research aims to determine: 1) the implementation of character development of students through an English literacy program based on storytelling, 2) the integration of character development of students through an English literacy program based on storytelling. This research used qualitative descriptive methods with data collection and analysis techniques through observation, interviews, and documentation. The subjects of this research were two teachers acting as model teachers and students from classes X-1 and X-3. The research was conducted at Madrasah Aliyah Negeri (MAN) 2 Kota Makassar in the first semester of the 2023/2024 academic year. Before conducting the research, the researcher and teachers discussed the implementation process of the learning, the timeline of activities, and the agreed-upon topics. The results of this research were as follows: 1) the implementation of character development began with a prayer before starting the English literacy program based on storytelling. It was then followed by reviewing narrative text material, Q&A sessions, assignment, and finally, performing storytelling to foster the characters of  discipline, hard work, responsibility, and creativity with a percentage ranging from 78.86 (good category) to 87.68 (very good category). This indicated that all students actively participated in each stage of the program, emphasizing the importance of character education, as clearly stated in Surah al-Qalam, verse 4. 2) English teachers at MAN 2 Kota Makassar have integrated character development into English language learning. It was included in lesson planning, material selection, media usage, classroom management, and assessment. In addition, English teachers have a comprehensive understanding of English language learning based on storytelling. This literacy program could foster the character of students as education and habituation in their daily activities.